An improved fuzzy-AHP (IFAHP) approach to compare SECI modes. Issue 15 (2nd August 2016) - Tyagi, Satish
Abstract : Mental models and knowledge base of an employee are two key resources of an organisation that are imperative to develop innovative products. Effective utilisation of socialisation (S), externalisation (E), combination (C) and internalisation (I) modes within any product development (PD) phase plays an important role in creating new knowledge and updating the mental models. In order to investigate the influence of SECI modes on a specific PD phase, an improved fuzzy analytical hierarchy process approach is presented. In simple fuzzy analytical hierarchy process, the numbers are either normalised or a zero value is assigned to the degree of possibility when two triangles are not intersecting with each other. This approach calculates distorted values of degree of possibility and thus very likely produces false ranking of alternatives. The article proposes to extend the triangle edges about x -axis until they intersect when the pessimistic value of one triangle is more than the optimistic value of other triangle. It allows developing a mathematical formulation to estimate the true values of degree of possibility instead of zero. An example of conceptual design phase is discussed to illustrate the applicability and usefulness of proposed framework. In order to evaluate the performance of underlying phase in terms of knowledge creation, five criteria are selected based on the literature search and discussion with subject matter experts from strategic decision areas. After stringent analysis and exhaustive experimentation, it is found that internalisation mode highly influences the conceptual design phase.